2015
DOI: 10.1111/mec.13133
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐sensitive fitness cost of insecticide resistance in Chinese populations of the diamondback moth Plutella xylostella

Abstract: Alleles conferring a higher adaptive value in one environment may have a detrimental impact on fitness in another environment. Alleles conferring resistance to pesticides and drugs provide textbook examples of this trade-off as, in addition to conferring resistance to these molecules, they frequently decrease fitness in pesticide/drug-free environments. We show here that resistance to chlorpyrifos, an organophosphate (OP), in Chinese populations of the diamondback moth, Plutella xylostella, is conferred by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 74 publications
4
59
0
Order By: Relevance
“…The fitness costs resulting from insecticide resistance are more or less dependent on environmental factors that have a great impact on life history traits; in particular, when the environment is unfavourable for insect development the estimated costs tend to be high. Environmental stressors such as high or low temperatures, parasitism and food quality were shown to have a negative effect on developmental time, fertility and mortality, thereby limiting population growth. Moreover, negative genetic trade‐offs can also be apparent in the absence of the insecticide or in the presence of sublethal doses .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fitness costs resulting from insecticide resistance are more or less dependent on environmental factors that have a great impact on life history traits; in particular, when the environment is unfavourable for insect development the estimated costs tend to be high. Environmental stressors such as high or low temperatures, parasitism and food quality were shown to have a negative effect on developmental time, fertility and mortality, thereby limiting population growth. Moreover, negative genetic trade‐offs can also be apparent in the absence of the insecticide or in the presence of sublethal doses .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . investigated the temperature effects on organophosphate (OP)‐resistant DBM strains and concluded that extremely cold or warm conditions are unfavourable for insect development and may also modify the fitness costs associated with pesticide resistance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations